Pengaruh Variasi Intesitas Cahaya Terhadap Efisiensi Fotosintesis Pada Pertumbuhan Tanaman - Waruwu, Arni Lestari; Mendrofa, Heppy Kardiani; Tafonao, Fedilina; Gulo, Namyra Olivia; Zai, Manyupril Lukevin Fatlow; Waruwu, Patricia Zeni Febriani; Gulo, Perti Citra Damarni; Zebua, Helmin Parida (Jurnal Ilmu Pertanian dan Perikanan, 2024)
This study examines the effect of varying light intensity on photosynthesis efficiency in plant growth. Photosynthesis is a vital process for plants, relying on solar energy to convert carbon dioxide and water into glucose and oxygen. The intensity of light received by plants significantly determines the efficiency of photosynthesis and plant growth. This research was conducted using a literature review method, analyzing various scientific sources to understand how light intensity affects the photosynthesis process. The results indicate that optimal light intensity enhances the rate of photosynthesis, while excessively low or high intensity can hinder plant growth. Other factors, such as light spectrum, light duration, and plant adaptation to specific light conditions, also influence photosynthesis efficiency.